2016
DOI: 10.17576/3l-2016-2201-07
|View full text |Cite
|
Sign up to set email alerts
|

(._.)/ dont 4get 2 txt me plz! Linguistic and Discoursal Features of Short Message Service by Female Texters

Abstract: The practicality and limited space of SMS have become features encouraging the emergence of various forms of SMS language. An analysis of SMS from 20 Acehnese female students in the University of Syiah Kuala was therefore carried out to inspect the elements of language employed within the text messages. The data of 110 SMS gathered through a mobile device were thoroughly analyzed and later categorized into linguistics and discoursal features. The result showed that female students tend to write about their psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Data 2 that produced by generation Y used some form of mumble such as hmhmhmhm for opening and sometimes to make sense of a statement. The finding is in line with [7] which states that logogram was to condense words. By using a logogram, it can be concluded that both generations (Gen-X and Gen-Y) want to convey the same message as when they delivered it when communicating face to face.…”
Section: Logogramsupporting
confidence: 89%
See 3 more Smart Citations
“…Data 2 that produced by generation Y used some form of mumble such as hmhmhmhm for opening and sometimes to make sense of a statement. The finding is in line with [7] which states that logogram was to condense words. By using a logogram, it can be concluded that both generations (Gen-X and Gen-Y) want to convey the same message as when they delivered it when communicating face to face.…”
Section: Logogramsupporting
confidence: 89%
“…This implies messaging likewise has talk markers of facial pictures framed using joined accentuation images that unequivocally demonstrate individuals' mentalities and emotions, for example, those found in talking styles. The information was then examined and arranged into the classes of phonetic and discoursal highlights of SMS by Crystal (2008) Heidari and Alibabaee (2013) and ) and Yusuf et al [7]. In the parts of phonetic highlights, we alluded to Crystal's ( 2008) and [7] characteristics; they are logogram, pictogram, overlooked letters, nonstandard spelling, initialism, shortening, and certifiable oddities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lakoff is not endorsing but simply describing a culture-wide ideology that scorns and trivializes both women and their ways of speaking, while scholars continue to debate the concept of women's language. As continuing until now, another study from Yusuf, Natsir, and Yusra (2016) have revealed that women's language is seen as inferior and something that stands out from the norm. Hence, there is a term called the feminist language, which refers to the effort, often of political and grassroots movements, to change how language is used to gender people, activities, and ideas on an individual and societal level.…”
Section: Introductionmentioning
confidence: 98%